Research on Mooring System under Static Equilibrium. Issue 3 (April 2021) - Chai, Wangyang; Liu, Yifan; Zhang, Ziyi; Tang, Jiaying; Zhang, Tong
Abstract: As an important treasure house of territorial resources, the ocean has been paid more and more attention in recent years. In this paper, according to the actual working situation of the transmission node of the near shallow water observation network, the anchor chain system, the steel barrel system, the steel pipe system and the buoy system are analyzed. The model is established through the connection between the systems, and then the model is improved according to the specific situation of the three problems. The state of each system is analyzed and solved, and the good design of the mooring system is given according to the data The scheme of calculation.